Distinguishing Sichuan Walnut Cultivars and Examining Their Relationships with Juglans regia and J. sigillata by FISH, Early-Fruiting Gene Analysis, and SSR Analysis - Luo, Xiaomei; Chen, Jingyuan (Frontiers in Plant Science, 2020)
Walnuts are economically important tree species in Sichuan Province (China) that provide heathy nuts. Fluorescence in situ hybridization (FISH) and analyses of an early-fruiting gene fragment and simple sequence repeats (SSRs) were used to distinguish Sichuan walnut cultivars and examine their relationships with Juglans regia L. and Juglans sigillata Dode. Thirty-four small chromosomes were counted in four Sichuan walnut cultivars. In the four cultivars, 5S rDNA was located in the proximal regions of two chromosomes (5 and 6), while (AG3T3)3 was located at both ends of each chromosome. The existence of the signal at both chromosome ends ensured accurate chromosome counts. 5S rDNA and (AG3T3)3 were not effective in identifying Sichuan walnut cultivars. Evolutionary analysis involving 32 early-fruiting nucleotide sequences from Sichuan walnut materials were performed with the maximum likelihood method. There were a total of 602 positions. All positions with gaps and missing data were eliminated, resulting in a final dataset of 562 positions. The ML tree with the highest log likelihood (-1607.82) revealed two obvious groups: one including materials of J. regia, which fruits 1 year after grafting, and another including materials of J. sigillata, which fruits >3 years after grafting. The early-fruiting gene fragment divided 10 walnut cultivars into two groups, indicating that it was somewhat effective for distinguishing Sichuan walnut cultivars. Furthermore, 22 SSR loci were revealed to identify nine walnut cultivars. Eight cultivars were exclusively discerned by one SSR locus each: Chuanzao 1 [CUJRB307 (116) or CUJRA206a (182)], Chuanzao 2 [JSI-73 (154)], Shuangzao [CUJRB103a (123), CUJRB218 (144), JSI-71 (146), or CUJRA206a (176)], Shimianju [ZMZ11 (138)], Meigupao [CUJRB218 (149), CUJRB103a (151), or CUJRA206a (190)], Muzhilinhe [CUJRB220 (136), ZMZ11 (147), CUJRC310 (156), or JSI-73 (166)], Maerkang [CUJRA124 (154), CUJRB218 (159), or CUJRA123 (182)], Yanyuanzao [CUJRA124 (150) or CUJRA206a (192)]. The Shuling cultivar was identified by the combination of ZMZ11 (148) and other SSR loci, which distinguished and excluded the Chuanzao 1 and Yanyuanzao cultivars. Our results will guide the identification and breeding of Sichuan walnut cultivars.